Influence of Rainfall Patterns on the Instability of Slopes - Muntohar, A.S.; Ikhsan, J.; Liao, H.J. (Institute of Research and Community Outreach - Petra Christian University, 2013)
The assessment of rainstorm-induced shallow landslides is still a research topic of wide concern for scientists and engineers. This paper examined the effect of rainfall intensity distribution on shallow landslides. Four synthetic rainfall distributions comprising uniformed, delayed, centralized, and advanced, were selected to examine the effect of rainstorm patterns on slope failure. The infiltration was modeled using Green-Ampt equation, while an infinite slope was selected to model the shallow landslide. Monte Carlo Simulation was applied to analyze the failure probability of the slopes. Two landslide cases were selected to examine the proposed model. The results indicated that among the four representative rainstorm patterns, the advanced rainfall pattern caused worst slope stability. The advanced rainfall pattern resulted in the shortest rainfall duration threshold for landslide occurrence, followed by the central, uniform, and then delayed rainfall pattern. The probabilistic analysis method was suitable to estimate the time of failure for the evaluated landslide cases.